2001
DOI: 10.1016/s0042-6989(00)00256-x
|View full text |Cite
|
Sign up to set email alerts
|

A model of eye movements and visual working memory during problem solving in geometry

Abstract: The Oculomotor Geometry Reasoning Engine (OGRE) was proposed to model eye movements and visual working memory during problem solving in geometry. OGRE postulates that geometrical elements from diagrams are added to visual working memory when they are scanned. Newly-added elements overwrite elements already in memory. The model was applied to eye-movement patterns of three subjects: two geometry experts and one non-expert. Their eye movements and verbal protocols were recorded as they solved geometry problems p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 15 publications
3
67
0
1
Order By: Relevance
“…Prior research on eye movements and problem solving has shown that overt attention can illuminate the cognitive processes involved in problem solving (Epelboim and Suppes, 2001; Knoblich et al, 2001, 2005; Grant and Spivey, 2003; Jones, 2003; Thomas and Lleras, 2007, 2009; Bilalić et al, 2008; Eivazi and Bednarik, 2010, 2011; Madsen et al, 2012, 2013a,b; Lin and Lin, 2014; Susac et al, 2014). However, we are particularly interested in two directions of causal relationships between overt attentional selection and the higher-level cognitive processes involved in problem solving: (1) the causal relationship starting from higher-level cognitive processes involved in problem solving and ending with attentional selection; and (2) the reverse causal relationship starting from attentional selection and ending with the higher-level cognitive processes involved in problem solving.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research on eye movements and problem solving has shown that overt attention can illuminate the cognitive processes involved in problem solving (Epelboim and Suppes, 2001; Knoblich et al, 2001, 2005; Grant and Spivey, 2003; Jones, 2003; Thomas and Lleras, 2007, 2009; Bilalić et al, 2008; Eivazi and Bednarik, 2010, 2011; Madsen et al, 2012, 2013a,b; Lin and Lin, 2014; Susac et al, 2014). However, we are particularly interested in two directions of causal relationships between overt attentional selection and the higher-level cognitive processes involved in problem solving: (1) the causal relationship starting from higher-level cognitive processes involved in problem solving and ending with attentional selection; and (2) the reverse causal relationship starting from attentional selection and ending with the higher-level cognitive processes involved in problem solving.…”
Section: Introductionmentioning
confidence: 99%
“…However, we are particularly interested in two directions of causal relationships between overt attentional selection and the higher-level cognitive processes involved in problem solving: (1) the causal relationship starting from higher-level cognitive processes involved in problem solving and ending with attentional selection; and (2) the reverse causal relationship starting from attentional selection and ending with the higher-level cognitive processes involved in problem solving. A relatively small number of studies have investigated each of these relationships, with some speaking more to the effect of higher-level cognitive processes in problem solving on attentional selection (Epelboim and Suppes, 2001; Knoblich et al, 2001; Madsen et al, 2012), and others speaking more to the effect of attentional selection on higher-level cognitive processes in problem solving (Epelboim and Suppes, 2001; Cameron et al, 2002; Grant and Spivey, 2003; Tai et al, 2006; Thomas and Lleras, 2007, 2009; Lin and Lin, 2014; Susac et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye movements of problem solvers have been studied [e.g. Epelboim & Suppes, 2001;Madsen et. al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…For over a decade, considerable effort had been devoted to investigating the relationship between VWM and eye movements (Bays & Husain, 2008;Epelboim & Suppes, 2001;Hodgson, Dittrich, Henderson, & Kennard, 1999;Postle, Idzikowski, Sala, Logie, & Baddeley, 2006;Soto, Humphreys, & Rotshtein, 2007). Our eye-tracking experiment results for the first time demonstrate a strong correlation between individual VWM capacity and eye-movement patterns in a nontrivial problem-solving scenario.…”
Section: Discussionmentioning
confidence: 72%